Extracellular vesicles enriched with an endothelial cell pro-survival microRNA affects skin tissue regeneration - Fernandes, Hugo (2022)
Endothelial cell (EC) activity is essential for tissue regeneration in several (patho)physiological contexts. However, our capacity to deliver in vivo biomolecules capable of controlling EC fate is relatively limited. Here, we screened a library of microRNA (miR) mimics and identified 25 miRs capable of enhancing the survival of ECs exposed to ischemia-mimicking conditions. In vitro, we showed that miR-425-5p, one of the hits, was able to enhance EC survival and migration. In vivo, using a mouse Matrigel plug assay, we showed that ECs transfected with miR-425-5p displayed enhanced survival compared with scramble-transfected ECs. Mechanistically, we showed that miR-425-5p modulated the PTEN/PI3K/AKT pathway and inhibition of miR-425-5p target genes (DACH1, PTEN, RGS5, and VASH1) phenocopied the pro-survival. For the in vivo delivery of miR-425-5p, we modulated small extracellular vesicles (sEVs) with miR-425-5p and showed, in vitro, that miR-425-5p-modulated sEVs were (1) capable of enhancing the survival of ECs exposed to ischemia-mimic conditions, and (2) efficiently internalized by skin cells. Finally, using a streptozotocin-induced diabetic wound healing mouse model, we showed that, compared with miR-scrambled-modulated sEVs, topical administration of miR-425-5p-modulated sEVs significantly enhanced wound healing, a process mediated by enhanced vascularization and skin re-epithelialization. © 2022 The Authors